PERAN DINAS SOSIAL PROVINSI JAWA TIMUR DALAM PROGRAM ASISTENSI SOSIAL PENYANDANG DISABILITAS PLUS (ASPD PLUS) - Puteri, Aisya Septia Cahyaning; Nawangsari, Ertien Rining (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2024)
The physical and mental limitations experienced by people with disabilities result in a lack of opportunities to carry out various activities in various aspects, so that this can affect the level of welfare for people with disabilities. The East Java Provincial Social Service has an important role in realizing and improving the welfare of people with disabilities, one of which is through the Social Assistance for People with Disabilities PLUS (ASPD PLUS) program. This research aims to determine the role of the East Java Province Social Service in the Social Assistance Program for Persons with Disabilities (ASPD PLUS). This research uses a descriptive method with a qualitative approach. The results of this research are to determine the success of the role of the East Java Province Social Service in the Social Assistance Program for Persons with Disabilities (ASPD PLUS) using the theory of Jim Ife and Frank Tesoriero (2014), namely: 1) Role of Facilitator, 2) Role of Education, 3) Role Representation, and 4) Technical Role. The results show that the East Java Provincial Social Service in the Social Assistance Program for Persons with Disabilities PLUS (ASPD PLUS) has carried out its role quite well and requires development so that it leads better in the future. Keywords: Service Role, Social Welfare, Persons with Disabilities, ASPD PLUS.